Factors that influecing participation in Gerakan PB1828 case study in Miri branch / Johanes Dana Thomas and Allan Kedit Frankonero - Thomas, Johanes Dana; Frankonero, Allan Kedit (2024)
This chapter consists ofseveral sections. Section 1.1 is on the chapter review; section 1.2 describes the factors influencing youth participation in Gerakan PBB 1828, a case study in Miri branch. Section 1.3 highlights the problem statement ofthis research. Section 1.4 research issues and gaps. Section 1.5 scope ofstudy, Section 1.6 significance ofstudy. Section 1.7 research objectives. Section 1.8 research questions whereby Section 1.9 research hypotheses. 1.10 definitions ofterm and Section 1.11 is on the summary.